Wybrane zagadnienia reformy postępowania egzekucyjnego w sprawach cywilnych - Zedler, Feliks (Wydział Prawa i Administracji UAM, 1989)
In his article the author determines the criteria the legislator should observe in carrying out works on the reform of executive proceedings in civil law cases. According to the author, the reform should lead to the regulation which would allow to reach in practice the ideal civil proceedings. In the author's opinion the ideal civil proceedings should secure the adequate legal protection to those who seek such a protection and at the same time should not infringe values protected in a given society, should be as little burdensome as possible to the parties and participants, and should be cheap and quick. The author concludes that in consequence of the adoption of those assumptions several changes in legal provisions would have to be introduced, especially the one precluding the examination of the merits of a case in executive proceedings.
Selected problems of executive proceedings in civil law cases